La prueba ilícita. Una cuestión de concepto - Calderón Arias, Emma (2021)
Illicit proof is an institution that has been being treated since the late 19th century. The terminology used for its study is varied, but the features of it are common despite the part of the world in which it is developing. It is generally defined as evidence resulting from the infringement of legal rules or, within them, fundamental rights. However, I start from the position that unlawful illicit proof is result of the violation of legal norms in general. What happens is that it usually treated linearly without delving into specific issues of its own concept. This responds to a kind of inertia shown in the doctrine when talking about the concept of it. The need for conceptual clarification of the illicit test noted, including guidelines that from legal theory and jurisprudence can help enrich such studies.